Reproducibility and Repeatability of Foveal Avascular Zone Area Measurements Using Swept-Source Optical Coherence Tomography Angiography in Healthy Subjects. Issue 3 (May 2017) - Mastropasqua, Rodolfo; Toto, Lisa; Mattei, Peter A.; Di Nicola, Marta; Zecca, Isaia A.L.; Carpineto, Paolo; Di Antonio, Luca
Purpose: To assess the reproducibility and repeatability of foveal avascular zone (FAZ) area measurements using swept-source optical coherence tomography angiography (SS-OCTA) in healthy subjects. Methods: Sixty-four eyes of 64 healthy volunteers were randomly subjected to FAZ area measurements using SS-OCTA by 2 examiners in 2 different sessions. Results: The FAZ areas measured by the first and second observer were 0.269 ± 0.092 mm 2 and 0.270 ± 0.090 mm 2, respectively. Within subjects, the coefficients of variations were 2.44% (95% confidence interval [CI] 1.95% to 2.93%) and 2.66% (95% CI 2.00% to 3.31%) for the first and second observers, respectively. The coefficient of repeatability average measurements of FAZ area were 0.021 mm 2 and 0.024 mm 2 . The intraclass correlation coefficient values were 0.993 (95% CI 0.989 to 0.996) and 0.991 (95% CI 0.986 to 0.995). Interobserver and intraobserver concordance correlation coefficients ranged from 0.998 (95% CI 0.997 to 0.999) to 0.999 (95% CI 0.998 to 0.999) and from 0.989 (95% CI 0.982 to 0.993) to 0.987 (95% CI 0.979 to 0.992), respectively. Conclusions: The FAZ area measurements by means of SS-OCTA showed high reproducibility and repeatability in healthy eyes.